Mentalizing partially mediates the association between attachment insecurity and global stress in preservice teachers - Schwarzer, Nicola-Hans; Dietrich, Lars; Gingelmaier, Stephan; Nolte, Tobias; Bolz, Tijs; Fonagy, Peter (Frontiers in Psychology, 2023)
Objective: Considering the fact that the teaching profession is a highly stressful occupational field and that teachers' personal characteristics such as ineffective coping strategies contribute to higher levels of stress, the objective of the present study was to investigate whether insecure attachment styles areis related to global stress experiences in preservice student teachers. Furthermore, it was examined whether this link is partially mediated by the preservice teachers' mentalizingthe capacity to perceive and consider one's own and others' behavior based on intentional mental states such as thoughts, feelings, or wishes.Methods: Data of this cross-sectional study came from 202 preservice student teachers using self-report instruments (attachment: Expectation in Close Relationships; mentalizing: Reflective Functioning Questionnaire; stress: Trier Inventory of Chronic Stress). The hypotheses were tested using structural equation modelling.Results: Anxious attachment was positively related to stress and impairments in mentalizing. In addition, the link between attachment-related anxiety and stress was partially mediated by mentalizing. Avoidant attachment was not associated with stress or mentalizing.Discussion: Results indicate that anxious attachment style is associated with higher perceived stress in preservice student teachers. Consequently, particularly attachment-related anxiety may be a risk factor which, in turn, may foster perceptions of higher global stress experiences.Additional research needs to focus on exploring the link between attachment insecurity and global stress experiences among preservice student teachers. An examination of preservice student teachers' own attachment experiences proves to be usefulfor example in the context of mentalization-based supervision or reflective practice.